2022
DOI: 10.9734/jeai/2022/v44i1030884
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Foliar Application of Chitosan on Growth, Yield and Nutritional Qualities of Red Amaranth (Amaranthus gangeticus L.)

Abstract: Chitosan is a promising natural biopolymer that stimulates growth, increases yield, and boosts-up plants' immune systems. A field experiment was conducted to study the effect of foliar application of chitosan on growth, yield and quality attributes (viz. chlorophyll-a, chlorophyll-b, total chlorophyll, carotenoids, total ash and major nutrient contents) of red amaranth. The field experiment was laid out in a Randomized Completely Block Design (RCBD) with three replications and six treatments [viz. T0 = Control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Where these results agree with what [28] found on the Rosa hybrid plant, spraying the plants with chitosan at the above concentration resulted in obtaining the largest significant values in the leaves content of total chlorophyll (Table 4) at the end of the experiment. This may be due to the action of chitosan in protecting the plant and increasing its resistance against diseases and their causes, as well as against insect pests, which is reflected in improving plant growth and increasing its activity, in addition to its role in improving the efficiency of the photosynthesis process and increasing its outputs as a result of its role in increasing the activity of enzymes that affect the process of photosynthesis thus lead to an increase in pigments in the plant [29,30], This is supported by [31] in their study on Amaranthus gangeticus. The results in Table (3) also indicated a significant increase in the number of branches when spraying plants with chitosan at the above concentration.…”
Section: Characteristics Of the Inflorescences Of Gerbera Produced Du...mentioning
confidence: 99%
“…Where these results agree with what [28] found on the Rosa hybrid plant, spraying the plants with chitosan at the above concentration resulted in obtaining the largest significant values in the leaves content of total chlorophyll (Table 4) at the end of the experiment. This may be due to the action of chitosan in protecting the plant and increasing its resistance against diseases and their causes, as well as against insect pests, which is reflected in improving plant growth and increasing its activity, in addition to its role in improving the efficiency of the photosynthesis process and increasing its outputs as a result of its role in increasing the activity of enzymes that affect the process of photosynthesis thus lead to an increase in pigments in the plant [29,30], This is supported by [31] in their study on Amaranthus gangeticus. The results in Table (3) also indicated a significant increase in the number of branches when spraying plants with chitosan at the above concentration.…”
Section: Characteristics Of the Inflorescences Of Gerbera Produced Du...mentioning
confidence: 99%
“…A similar result was also reported by Razavizadeh and Adabavazeh [31]. On the contrary, several studies reported a positive effect, in both pot and field conditions, viz., Nasrin et al [20] reported that the highest root length (18.16 cm) of red amaranth was obtained from the foliar application of chitosan at the rate of 300 ppm, while the lowest root length (14.38 cm) was recorded from the control plant. Similar to this, González Gómez et al [32] found that the root length of grafted watermelon was increased by chitosan-polyvinyl alcohol hydrogels with absorbed copper nanoparticles.…”
Section: Root Lengthmentioning
confidence: 99%
“…On the other hand, the lowest yield of spinach (7.53 kg per plot) was obtained from the control treatment (Table 1). Several studies reported that foliar spraying of chitosan has a significant positive effect on yield and yield-contributing characteristics of red amaranth and tomatoes [20,21,28]. Similarly, numerous studies have found that spraying chitosan onto plant leaves significantly improves yield and yield-contributing traits in maize [33], and watermelon [32].…”
Section: Total Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo investigations have shown that chitosan treatment can delay the postharvest deterioration of fruits and vegetables [24,25]. Despite the many beneficial effects of chitosan on the post-harvest quality of vegetables only a few studies have been conducted so far on the effect of chitosan on the post-harvest quality of vegetables and fruits in Bangladesh [24,[26][27][28]. Moreover, studies are very limited regarding the effect of chitosan on the post-harvest shelf life, biochemical properties and nutrient content of carrots in Bangladesh for its successful application as a vegetable coating.…”
Section: Introductionmentioning
confidence: 99%